Dopamine neurons in the ventral periaqueductal gray modulate isoflurane anesthesia in rats. (2nd September 2020) - Liu, Chengxi; Zhou, Xiao; Zhu, Qiuyu; Fu, Bao; Cao, Song; Zhang, Yu; Zhang, Lin; Zhang, Yi; Yu, Tian
Abstract: Aims: General anesthesia has been applied in surgery for more than 170 years, and there is little doubt that GABAA receptors have an important role as anesthetic molecular targets, but its neural mechanisms remain unclear. Increasing researchers have shown that dopaminergic pathways in the brain are crucial for sleep and wake. General anesthesia‐induced unconsciousness and natural sleep share some neural correlates. However, the role of GABAA receptors in ventral periaqueductal gray (vPAG) dopamine (DA) neurons in the isoflurane‐induced unconsciousness has yet to be identified. Methods: In the present study, we used calcium fiber photometry recording to explore that the activity of ventral periaqueductal gray (vPAG) neurons. Then, rats were unilaterally microinjected with 6‐hydroxydopamine into the vPAG area to determine the role of vPAG‐DA neurons in isoflurane‐induced‐anesthesia. Furthermore, thirty SD rats were divided into three groups: a GABAA R agonist‐muscimol group, a GABAA R antagonist‐gabazine group, and a control group. Finally, whole‐cell patch clamp was used to examine the effects of isoflurane and GABAA receptor agonist/antagonist on vPAG‐DA neurons. Results: The vPAG neurons were markedly inhibited during isoflurane anesthesia induction and that these neurons were activated during emergence from isoflurane anesthesia. Lesion to the vPAG‐DA neurons shortened the induction time and prolonged the emergence time while increasing δ power in isoflurane anesthesia. Intracerebral injection of the GABAA receptor agonist (muscimol) into the vPAG accelerated the induction of anesthesia and delayed recovery from isoflurane anesthesia, with a decrease of δ power and an augment of β power. Injection of GABAA receptor antagonist gabazine generated the opposite effects. Isoflurane enhanced GABAergic transmission, and GABAA receptor agonist partly increased isoflurane‐induced inhibition of vPAG‐DA neurons, while GABAA receptor antagonist evidently attenuated GABAergic transmission. Conclusion: Our results suggest that vPAG‐DA neurons are involved in isoflurane anesthesia through activation of the GABAA receptor. Abstract : General anesthesia has been widely applied in surgery for more than 170 years. However, its underlying mechanisms are still a mystery. It was reported that dopaminergic pathways in the brain are crucial for the emergence from general anesthesia. We previously also found that reductions of ventral periaqueductal gray (vPAG) dopaminergic neurons numbers shortened the induction time and prolonged the emergence time from propofol anesthesia. However, the role of GABAA receptor in ventral periaqueductal gray (vPAG) dopamine (DA) neurons in the isoflurane‐induced unconsciousness has yet to be identified. Here, using real time in vivo fiber photometry, we found that neuronal activity in the vPAG was markedly disinhibited during the recovery from isoflurane anesthesia. Subsequently, microinjection of 6‐hydroxydopamine (6‐OHDA) into the vPAG to selectively kill DA neurons shortened the induction time and prolonged the emergence time, with an increase of δ‐band power in cortical electroencephalogram (EEG). Then, microinjection of GABAA receptor selective agonist (muscimol) into the vPAG notably accelerated the induction of anesthesia and delayed recovery from isoflurane anesthesia, with a decrease of δ power and an augment of β power. Microinjection of GABAA receptor antagonist (gabazine) generated the opposite effects. Finally, whole‐cell patch clamp was applied to further explore the cellular mechanism underlying modulation of GABAA receptor on vPAG‐DA neurons under isoflurane anesthesia. Our data demonstrated that the frequency of spontaneous inhibitory postsynaptic current (sIPSC) of vPAG‐DA neurons was enhanced by isoflurane. GABAA receptor agonist enhanced the effect of isoflurane on sIPSC, and its actions were eliminated by application of gabazine. Collectively, these results indicate that isoflurane activates GABAA receptor to affect GABA neuron and vPAG‐DA neurons. Then, isoflurane directly suppressed the activity of wake‐promoting vPAG‐DA neurons to induce anesthesia or activate GABA neuron to indirectly inhibit vPAG‐DA neurons causing the reduction of DA. Our results suggest that vPAG‐DA neurons are involved in isoflurane anesthesia through activation of the GABAA receptor.